Ecological assessment of Portuguese reservoirs based on littoral epilithic diatoms - Novais, Maria Helena; Blanco, Saúl; Delgado, Cristina; Morais, Manuela; Hoffmann, Lucien; Ector, Luc (Springer, 2012)
The objective of this study was to evaluate whether biological methods based on epilithic littoral diatoms are a valuable complement to other biological elements for the assessment of the ecological potential of reservoirs in Portugal, in accordance with the requirements of the European Water ramework Directive. The statistical analysis performed (PCA,DCA, ANOSIM and SIMPER) based on the study of diatom communities of 18 reservoirs allowed the following results: (i) the separation of all the a priori defined types (North, Main Courses and South) was proved; (ii) there were no significant differences between reservoirs classified as reference and nonreference and (iii) the classification of the reservoirs as reference or non-reference based on the use of the diatom Specific Pollution sensitivity Index as a omplementary variable allowed the definition of Maximum Ecological Potential reservoirs for the North and South types. Methods based on the use of epilithic littoral diatoms can therefore contribute,together with other biological elements, for the assessment of the ecological potential of aquatic lentic systems in Portugal, almost exclusively constituted by reservoirs.
Keywords: Epilithon; Heavily modified water bodies; Littoral diatoms; Portugal; Water Framework Directive